A systematic approach to experimental modeling and assessment of elastic actuators by component-wise parameter identification - Lendermann, M.; Stuhlenmiller, F.; Erler, P.; Rinderknecht, S.; Beckerle, Philipp (IEEE International Conference on Intelligent Robots and Systems, 2015)
This paper presents a systematic approach for experimental identification and assessment of mechanical effects on the dynamics of elastic actuators. The variable torsion stiffness (VTS) actuator is used as an example. As a basis for parameter identification, a flexible joint robot model considering friction and damping is used. To identify and assess occurring effects, a component-wise experimental investigation of the VTS drive train is performed. In this, influences of friction and inertia are examined using numerical least-squares regression to identify link inertia, friction in bearings, stiffness and damping in the elastic element, and the friction of gear box and actuator based on measured data. Comparing simulations to measured data, allows an evaluation of the obtained particular parameters and an assessment of their impact on overall system dynamics. Hence, the component-wise procedure enables to decide if those should be considered. This approach can be generalized to other elastic actuators by adapting model structure and/or performed experiments.
CRIS-Team Scopus Importer:2021-09-24